CIS Countries Foreign Economic Activity — from Challenges to New Opportunities - M. S. Goncharov (Евразийская интеграция: экономика, право, политика)
Aim and tasks. To identify current trends and issues in foreign trade, the international financial system, and the investment activity of CIS member states, and to provide recommendations that contribute to sustainable economic development and strengthened mutual cooperation.Methods. Utilized statistics from the external sectors of CIS economies from 2019 to 2023. Methods of aggregation, comparison, retrospective, and indicative analysis were applied to the data. Graphical representation of indicators allowed for visualization of key trends in the studied metrics, calculated from data provided by the Interstate Statistical Committee of the CIS, the World Bank, UNCTAD, and the Brookings Institution.Results. In recent years, the CIS has faced several global shocks that have affected the international economic relations of its members with each other and with third countries. Despite external destabilizing influences and geopolitical turbulence, CIS member states maintain resilience and a positive development trajectory, largely due to mutually beneficial cooperation with Russia — an essential economic partner. Russia holds a leading position in mutual trade with CIS countries, and the reorientation of Russian exports to “friendly” countries has stimulated regional trade turnover. The burden of external debt for CIS national economies is decreasing, and their debt stability and solvency are normalizing. Less positive situation is in direct investment flows, which remain unstable and unevenly distributed among countries.Conclusions. In the context of individual national economies, it is fair to note that the complex geopolitical environment and unprecedented external economic pressures narrow opportunities for economic growth and sustainable development. However, this statement is not always true for interstate associations, and CIS member states are a prime example of this. Currently, during a challenging period that requires solidarity and mutual support from participants, the potential of this union can be fully realized. A thorough study of the issue can reveal numerous promising areas for mutually beneficial cooperation in trade, credit, and investment relations. It is necessary to eliminate integration barriers to transform the CIS into a powerful and influential international organization.